2022
DOI: 10.3389/fpls.2022.892630
|View full text |Cite
|
Sign up to set email alerts
|

GhCalS5 is involved in cotton response to aphid attack through mediating callose formation

Abstract: Callose synthase plays an essential role in plant growth and development and in response to all sorts of stresses through regulating callose formation. However, few research about the function and mechanism of the insect resistance of callose synthase genes have been reported in cotton. In this study, a cotton callose synthase gene GhCalS5 was cloned, and its function and mechanism of resistance to cotton aphids were analyzed. The expression of GhCalS5 was significantly upregulated in both, leaves and stems of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Herbivorous aphids penetrate the phloem through their stylets (needle-like mouthparts) to suck plant juice, and plants block the phloem by accumulating callose on the sieve plates ( Will et al., 2013 ; Jaouannet et al., 2014 ). The GhCalS5 gene in cotton ( Gossypium hirsutum ) was induced after aphid feeding and was involved in cotton resistance against aphid attack by mediating callose accumulation ( Mbiza et al., 2022 ). Again, a potential effector NlG14 of the brown planthopper Nilaparvata lugens could trigger the accumulation of reactive oxygen species and callose to enhance rice response to both insects and microbe pathogens ( Gao et al., 2022 ; Gao et al., 2023 ).…”
Section: Diverse Role Of Callose Function In Plant Development and De...mentioning
confidence: 99%
“…Herbivorous aphids penetrate the phloem through their stylets (needle-like mouthparts) to suck plant juice, and plants block the phloem by accumulating callose on the sieve plates ( Will et al., 2013 ; Jaouannet et al., 2014 ). The GhCalS5 gene in cotton ( Gossypium hirsutum ) was induced after aphid feeding and was involved in cotton resistance against aphid attack by mediating callose accumulation ( Mbiza et al., 2022 ). Again, a potential effector NlG14 of the brown planthopper Nilaparvata lugens could trigger the accumulation of reactive oxygen species and callose to enhance rice response to both insects and microbe pathogens ( Gao et al., 2022 ; Gao et al., 2023 ).…”
Section: Diverse Role Of Callose Function In Plant Development and De...mentioning
confidence: 99%
“…Deposition of lignin and callose in the cell wall is important for plant defence against pathogen invasion as these components form a physical barrier to prevent the diffusion of pathogen‐produced toxins (Guo et al., 2016 ; Huang et al., 2021 ; Mbiza et al., 2022 ; Zhang et al., 2019 ). We asked if GbCML45 and GbCML50 play a role in lignin accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…We found that lignin and callose accumulation was significantly reduced in stems of GbCML45 ‐ and GbCML50 ‐silenced cotton plants after V. dahliae inoculation (Figure 7d ), which might contribute to the weakened resistance of the silenced plants to V. dahliae infection (Figure 7a ), because the accumulation of lignin and callose is well known to contribute to enhanced resistance against V. dahliae in cotton through reinforcing cell wall structure (Huang et al., 2021 ; Mbiza et al., 2022 ; Xu et al., 2011 ). Similar results were also observed in other plant species in response to pathogen infection.…”
Section: Discussionmentioning
confidence: 98%
“…Sucrose synthase can directly convert the carbon in sucrose into cellulose or callose synthase in the plasma membrane. The appearance of the callose content peak may be an important sign that the secondary wall of the fiber cells has begun to thicken [ 36 ]. For all the DEGs we identified, clusters that were highly expressed during the SCW period were significantly enriched in sugar metabolism, the pentose phosphate pathway, butanoate metabolism, and the fructose and mannose metabolism signaling pathways.…”
Section: Discussionmentioning
confidence: 99%